What Aspects of Religiosity are Associated with Values? - Schwadel, Philip (Journal for the scientific study of religion, 2022)
A large body of research shows that religiosity in general is associated with values. Yet, we know little about the specific aspects of religiosity that drive this association. Using nationally representative data from a sample of young adults in the United States, we examined how various aspects of religiosity—religious tradition, service attendance, frequency of prayer, religious salience, belief in God, closeness to God, and number of religious friends—are associated with the 10 values comprising Schwartz's circle of values. Bivariate results indicate that most measures of religiosity are correlated with Schwartz's circle of values. Multivariate regression results, however, show that the relationship between religiosity and values is largely due to the positive associations between closeness to God and social focus values, the positive associations between number of religious friends and social focus values, and the negative associations between religious service attendance and personal focus values. We conclude by discussing why these aspects of religiosity appear to be most relevant to Schwartz's circle of values and by suggesting directions for future research on religiosity and values.